A morphologic and quantitative comparison of mechanoreceptors in the tibial remnants of the ruptured human anterior cruciate ligament. Issue 5 (February 2017) - Sha, Lin; Xie, Guoming; Zhao, Song; Zhao, Jinzhong
Abstract : Abstract: Reconstruction of the ruptured anterior cruciate ligament (ACL) does not always result in expected successful outcome. A satisfactory outcome depends not only on the tightness or strength of the graft but also on the quality of proprioceptive restoration. Mechanoreceptors of ACL are supposed to play considerable roles in the proprioceptive feedback system of knee. This study aimed to observe the condition and number of the surviving mechanoreceptors in the tibial remnant of ruptured ACL in human knees. From April 2009 to January 2012, 60 patients with existing free tibial remnants who had undergone arthroscopic ACL reconstruction were enrolled and divided into 4 groups according to the time duration of injury to surgery (Group I: no more than 3 months; Group II: 3 to 6 months; Group III, 6 months to 1 year; Group IV: more than 1 year). Six normal ACL specimens were taken as controls. Specimens were obtained from ACL tibial remnant and stained by the immunohistochemical staining method. The type, size, and quantity of mechanoreceptors were observed under the light microscope. A total of 92 Ruffini-like corpuscles, 9 Pacini-like corpuscles, 5 unclassified neural endings, and free nerve endings were identified via immunohistochemical staining. There were no significant differences in the number of mechanoreceptors in the 5 groups ( P  = 0.238). Some degenerative changes were observed in Group IV. The results suggest that the residual mechanoreceptors in the ruptured ACL exhibit long-term survival and showed no obvious signs of withering within 1 year. Residual mechanoreceptors do exist in the tibial remnants of ruptured anterior cruciate ligament in human knees and identified clearly by using immunohistochemistry staining. No significant difference was found regarding quantitative variation of the residual mechanoreceptors about the injury duration.